(untitled) (International Journal of Physiology, 2020)
The effects of various breathing manoeuvres on autonomic functions, especially those of alternate nostril breathing and single nostril breathing have been well documented.1,2,3,4 However, most of the studies have investigated these effects after practiced breathing manoeuvres,5,6,7 and few have looked into the immediate effects of such types of breathing. The purpose of this study was to determine the immediate effects of a single session of single nostril breathing, first right nostril and then left nostril, on the various time and frequency domain parameters of heart rate variability (HRV) and to compare these effects with that of HRV during normal breathing. Sixty male volunteers (age range, 20 to 40 years) were assessed. Electrocardiography was conducted, using standard procedure, under controlled laboratory conditions, for three five-minute periods: during breathing normally through both nostrils, during the last five minutes of a twenty-minute session of breathing through the right nostril only and similarly while breathing through the left nostril only. The R-R intervals obtained were analyzed for HRV parameters and further analyzed using different statistical method. When compared to right nostril breathing, a statistically significant increase in mean R-R intervals was noted with left nostril breathing (p = 0.009). Sympathetic activation with right nostril breathing was also evident, although statistically not found to be significant. A statistically significant higher SDNN with left nostril breathing as compared to both nostril breathing (p = 0.004) was also observed. Similarly, NN50 and pNN50 were found to be significantly higher with left nostril breathing as compared to both nostril breathing (p = 0.003 & 0.007, respectively). However, RMSSD, LF power, HF power, LF norm, HF norm and LF/HF ratio were not found to be statistically different for the three breathing manoeuvres. Thus our study showed an overall parasympathetic predominance, with an increase in total power of HRV with left nostril breathing, but the minute variations of HRV were not found to be significantly different among the three breathing manoeuvres.